Improving Research on the Psychology of Sustainable Consumption: Some Considerations from an Early Career Perspective. (5th February 2020) - Richardson, Lucy M.; Ginn, Joel; Prosser, Annayah M. B.; Fernando, Julian W.; Judge, Madeline
Abstract: Psychological research on sustainable consumption is developing a rich and diverse corpus of knowledge and tools, involving a broad range of disciplines. This very growth and diversity, however, poses challenges to our collective ability to build upon past research and progress in the field. We aim to place a selection of these challenges in the spotlight for discussion. In particular, we highlight some of the salient difficulties for early career researchers in psychology who are entering this field. Based on issues raised at a workshop conducted as part of the Psychology of Sustainable Consumption Small Group Meeting of the Society for the Psychological Study of Social Issues and the Society of Australasian Social Psychologists in 2018, we first examine challenges associated with working in transdisciplinary teams, measurement quality, data accessibility, and research dissemination. We then propose several options to address these, ranging from actions individual researchers can take, to more systemic changes.